2012
DOI: 10.5141/jefb.2012.010
|View full text |Cite
|
Sign up to set email alerts
|

Use of the foraging area by captive bred oriental storks (Ciconia boyciana) in a closed semi natural paddy field

Abstract: Rice paddy fields have been recognized as an alternative habitat for avian wetland foragers, and fish-rice farms have become a new tool in improving the abundance of aquatic animals. However, the use of the habitats by avian foragers, particularly by oriental storks (Ciconia boyciana), was not well understood. In the present study, we investigated how a fish-rice farm influenced the abundance of aquatic animals and documented the foraging behavior of the two captive bred oriental storks in a closed semi-natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Thus, they were selected as the objects of study in this work. According to the living habits of the study species, they can only inhabit and forage in water areas of depth between 0-40 cm [15][16][17][18]. Thus, the present work considers the water area with this as a suitable habitat for them.…”
Section: Model Establishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they were selected as the objects of study in this work. According to the living habits of the study species, they can only inhabit and forage in water areas of depth between 0-40 cm [15][16][17][18]. Thus, the present work considers the water area with this as a suitable habitat for them.…”
Section: Model Establishmentmentioning
confidence: 99%
“…They generally live in marshes or shallow water areas having a water depth below their tarsus (40 cm) [13][14][15][16]. Further, due to the limitations of their body size, especially the length of their beak, legs, and neck, they generally feed in shallow water areas having a depth of less than 40 cm, such as reed marshes and fish ponds [15][16][17][18]. Further, they cannot survive in regions with very less water, as they need to put much effort to find food or cannot peck out food at all [14].…”
Section: Introductionmentioning
confidence: 99%
“…As Yoon et al () reported Oriental White Storks are now well known to forage in rice paddies and for the species, rice paddies have been recognized as an alternative wetland habitat (Ma, Cai, Li, & Chen, ), and they have become an important landscape feature for wetland species. Dynamic habitat change from wetland to rice paddies was also observed in geese ( Anser albifrons ) in Japan, owing to the reclamation of wetlands (Moriguchi, Amano, & Ushiyama, ).…”
Section: Discussionmentioning
confidence: 99%
“…Today, Oriental White Storks are well known to forage in rice paddies (Yoon et al, ). Naito and Ikeda () reported that the species spent about 80% of its foraging time in rice paddies in June—the maximum for the year—and they have been witnessed foraging in shallow pools in the paddies (Ezaki & Miyara, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation